QUO VADIS PENDIDIKAN MULTIKULTURAL DALAM ERA GLOBAL DI PESANTREN - Choiri, Moh Miftahul (IAIN Ponorogo, 2011)
Historically, schools are educational institutions that are identical to the meaning of the typical Islamic Indonesia. As an educational institution